Rancang Bangun Smart Feeder Terintegrasi Monitoring Kualitas Air Bertenaga Surya Berbasis IoT pada Budidaya Perikanan - Elvinda Bendra Agustina; Dian Arif Rachman; Yusril Ihza Tachriri; Jessika Artamevira; Khusfiatul Kholisah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study presents the design and implementation of a smart feeder system integrated with real-time water quality monitoring powered by a solar photovoltaic system and based on the Internet of Things (IoT). The system automatically dispenses fish feed and monitors key water quality parameters such as pH, temperature, and Total Dissolved Solids (TDS). The ESP32 microcontroller was used as the main controller, integrated with multiple sensors and an MQTT-based monitoring application. The entire system is powered by a 30 Wp solar panel and a 12 V battery, enabling autonomous operation in remote areas without grid access. Experimental results show that motor rotation speed significantly affects feed distribution. The optimal feeding performance was achieved at medium motor speed with a feed distance of 8 m, ensuring uniform feed dispersion and low energy consumption (±14.4 W). Water quality parameters remained within the ideal range for freshwater aquaculture: pH 6.6–6.9, temperature 27.5–28.8 °C, and TDS 380–450 ppm. The photovoltaic system generated around 90–110 Wh/day, meeting the system’s daily energy demand (±45 Wh/day). This integrated IoT–solar solution demonstrates high efficiency and sustainability, suitable for rural aquaculture applications.